Munnstell og munnhygiene til medisinske pasienter. En kartlegging blant sykepleiere i medisinsk avdeling - Nina Karlsen; Birgit Brunborg (Septentrio Academic Publishing, 2017)
Oral care and oral hygiene in hospitalized patients. A survey of nurses in medical ward   In this study, we assessed whether an educational program for nurses in a medical ward could enhance their knowledge, attitude and documentation level of oral care procedures. We collected quantitative data before and after the educational program, using a questionnaire. The findings indicate an increase in the nurses' assessment of the elderly's oral status and need for oral care. The nurses became more conscious about common oral practice, and the need for proper equipment. Nurses' attention to oral care was low when workload was high, and their documentation of oral case was generally insufficient. The study concludes that improving nurses' oral care practice would be beneficial for patients, and that nurses' knowledge, attitude and documentation can be influenced through educational programs. Based on these findings, we recommend that mouth care programs be developed and followed up by quality assurance processes and scientific studies.